STRATEGIES FOR CONFLICT PREVENTION (METHODS FOR REACHING AGREEMENTS AND CONDUCTING NEGOTIATIONS; ENHANCING SOFT SKILLS AND COMPATIBILITY; MONITORING CONFLICTS IN PROJECT MANAGEMENT SYSTEMS) (Journal of Science-Innovative Research in Uzbekistan, 2025)
This article discusses conflict prevention strategies, methods for reaching agreements and conducting negotiations, improving ijtimoiy ko’nikmalarand alignment, as well as monitoring conflicts in project management systems. Reducing conflicts within project teams and implementing effective measures against them can enhance project outcomes and improve the teamwork environment. The article presents the necessary methods and approaches for applying these strategies in practice.